Prevalence of disruptive selection predicts extent of species differentiation in Lake Victoria cichlids. Issue 1871 (31st January 2018) - van Rijssel, Jacco C.; Moser, Florian N.; Frei, David; Seehausen, Ole
Abstract : Theory suggests that speciation with gene flow is most likely when both sexual and ecological selection are divergent or disruptive. Divergent sexual and natural selection on the visual system have been demonstrated before in sympatric, morphologically similar sister species of Lake Victoria cichlids, but this does not explain the subtle morphological differences between them. To investigate the significance of natural selection on morphology during speciation, we here ask whether the prevalence of disruptive ecological selection differs between sympatric sister species that are at different stages of speciation. Some of our species pairs do ( Pundamilia ) and others do not ( Neochromis ) differ distinctively in sexually selected male nuptial coloration. We find that (i) evidence for disruptive selection, and for evolutionary response to it, is prevalent in traits that are differentiated between sister species; (ii) prevalence of both predicts the extent of genetic differentiation; and (iii) genetic differentiation is weaker in species pairs with conserved male nuptial coloration. Our results speak to the existence of two different mechanisms of speciation with gene flow: speciation mainly by sexual selection tightly followed by ecological character displacement in some cases and speciation mainly by divergent ecological selection in others.